High School Students’ Ability with Translation Among Mathematical Representations in Solving the HOTS-Based Problems - Rahmawati, Azizah Nur Laily; Sa’dijah, Cholis; Anwar, Lathiful (Jurnal Pendidikan MIPA, 2022)
Translation is considered as a step in transforming the information contained from the source representation to the destination representation. In the process of students doing mathematical translation there are four stages of activity, Unpacking the Source, Preliminary Coordination, Constructing the Target, and Determining Equivalence. This study aims to analyze the activities carried out by students in translating representations from graphic to symbolic, table to symbolic, and verbal to symbolic based on HOTS. This research was conducted at SMA Lamongan Regency with three research students in class XI who had learned about the concept of quadratic functions. The instruments used were translation questions and interview guidelines. The applied data analysis focused on four stages of translation activity which were then grouped according to (high, medium, and low categories). The results showed that the translation of verbal representations into symbolic ones was the most difficult for students to complete.Keywords: mathematical translation, representation, HOTS.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1887-1899